Legal Responsibility of Instrumental Witnesses in the Process Making Authentic Deeds - Onetra, Rico; Arifulloh, Achmad (TABELLIUS: Journal of Law, 2025)
Abstract. This study aims to analyze: 1) the legal certainty of instrumental witnesses in the process of making authentic deeds. 2) the legal responsibility that can be imposed on instrumental witnesses if there is a discrepancy or untruth in the contents of the authentic deeds made. This type of research is normative legal research. The approach method in this research is the Statute approach. The type of data in this research is secondary data sourced from primary, secondary and tertiary legal materials. The data collection method uses library techniques (study documents). The analysis in this research is prescriptive. The results of the study conclude: 1) The legal certainty of instrumental witnesses in the process of making authentic deeds is the main pillar in guaranteeing the formal validity and perfect evidentiary value of deeds made by notaries. Legal certainty demands that every authentic deed must be formed in accordance with the provisions of applicable laws, including the requirement for the presence of two instrumental witnesses as regulated in Article 16 paragraph (1) letter m and Article 40 paragraph (1) UUJN. These provisions are imperative and must be fulfilled, because without the presence of a valid instrumental witness, the deed made by a notary does not fulfill its formal elements and cannot be qualified as an authentic deed. 2) The legal responsibility that can be imposed on the instrumental witness if there is a discrepancy or untruth in the contents of the authentic deed made lies in the formal aspects of the formation of the deed, not in the substance or content of the deed. This responsibility can be in the form of civil liability if the act results in loss to another party (through an unlawful act), criminal liability if proven to be consciously involved in forgery, providing false information, or stating to be present when not present during the process of reading and signing the deed, and administrative or ethical liability if there is a violation of notarial procedures and rules.Keywords: Accountability; Authentic Deed; Instrumental Witness.